Uji validitas dan reliabilitas instrumen penelitian: Kuesioner pola makan pada penderita gout arthritis - Putri, Marshanda Asfriani; Kuhon, Frelly Valentino; Palandeng, Henry Malcom Frank (Jurnal Kedokteran Komunitas dan Tropik, 2024)
Background: Globally, the prevalence of gouty arthritis has doubled from 1990 to 2020, with the total of number cases 55,8 million in 2020. There is no Indonesian national data, yet, studies in some regions noted the cases, in North Sulawesi, in Depok, and in Bali. Prevention of gouty arthritis involves a healthy diet and lifestyle. Knowing the knowledge, attitudes, and practice about diet in people with gouty arthritis can help health institutions plan more appropriate interventions to prevent an increase in cases. To assess this, a valid and reliable instrument to measurement is needed. Aim: To test validity and reliability of a questionnaire of knowledge, attitudes, and practice towards to diet in people with gouty arthritis. Methods: This study is a descriptive study with a quantitative approach involving 13 respondents, patients in Manado City Health Center selected using purposive sampling method. Validity was assessed using r-count obtained through bivariate Pearson which was compared with r-table. Reliability was assessed through Cronbach's alpha coefficient. Results: The validity test using bivariate Pearson was valid for 9 statement in knowledge and attitudes section, and 8 statement in practice section of the questionnaire, with r-count>r-table, and the reliability test using Cronbach's alpha with values on knowledge, attitudes, and actions of 0.906, 0.924, and 0.864, ≥0.7, respectively. Conclusion: 26 out of 30 valid and reliable questions can be used to measure the level of knowledge, attitudes, and practice in people with gouty arthritis. Keywords: gouty arthritis, questionnaire, validity, reliability